IMPLEMENTASI PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN DI MI MITRA PGMI STAIN PONOROGO - Fu’adi, Athok (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This study aimed to describe the implementation of active learning, creative, effective and fun at MI Partners PGMI STAIN Ponorogo which include: 1) preparation PAKEM learning, 2) implementation PAKEM learning, 3) PAKEM learning assessment, and 4) factors inhibiting and supporting learning PAKEM. This research is a qualitative research subject was a teacher at MI Partners Ma'arif Polorejo and Setono. Research instrument is the researcher himself. Data were collected through interviews, observation, documentation. The validity of data obtained by performing triangulation and constant observation. Data analysis was performed since the data were collected using an interactive model that consists of three stages, namely data reduction, data entry, and conclusion. The results showed that the preparation of learning PAKEM, found some teachers had not made in accordance with the characteristics of RPP PAKEM, this is because the model was still hung up on previous learning. Implementation of the learning PAKEM already running but not fully performed by all classes, only a few classes. Implementation of assessment, and classroom-based assessment using 3 domains, cognitive, affective and psychomotor, but to apply all that trouble. Barriers and support in learning PAKEM, obstacle lies in the teachers themselves and infrastructure facilities in the form of instructional media, while support from all stakeholders.Keywords: active, creative, and effective learning (PAKEM), Madrasah